2017
DOI: 10.18632/oncotarget.16221
|View full text |Cite
|
Sign up to set email alerts
|

Unique properties of thymic antigen-presenting cells promote epigenetic imprinting of alloantigen-specific regulatory T cells

Abstract: Regulatory T cells (Tregs) are potential immunotherapeutic candidates to induce transplantation tolerance. However, stability of Tregs still remains contentious and may potentially restrict their clinical use. Recent work suggested that epigenetic imprinting of Foxp3 and other Treg-specific signature genes is crucial for stabilization of immunosuppressive properties of Foxp3+ Tregs, and that these events are initiated already during early stages of thymic Treg development. However, the mechanisms governing thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 73 publications
4
22
0
Order By: Relevance
“…Slightly higher frequencies were detected on mTECs and t-DCs isolated from BALB/c mice, suggesting that under steady-state conditions a fraction of thymic APCs can sense IL-1. We previously have reported that Il1a and Il1b mRNA is expressed in the thymus under steady-state conditions with t-DCs showing higher expression levels as compared to mTECs 6 . Here, we analysed the presence of both cytokines in the thymus on protein level using thymic lysates and could demonstrate that under steady-state conditions both IL-1 and IL-1 are present in the thymus, in the range of 5-15 pg/ml (Figure 4b).…”
Section: In the Thymus Il-1r1 Is Mainly Expressed By Thymic Apcs Undmentioning
confidence: 93%
See 1 more Smart Citation
“…Slightly higher frequencies were detected on mTECs and t-DCs isolated from BALB/c mice, suggesting that under steady-state conditions a fraction of thymic APCs can sense IL-1. We previously have reported that Il1a and Il1b mRNA is expressed in the thymus under steady-state conditions with t-DCs showing higher expression levels as compared to mTECs 6 . Here, we analysed the presence of both cytokines in the thymus on protein level using thymic lysates and could demonstrate that under steady-state conditions both IL-1 and IL-1 are present in the thymus, in the range of 5-15 pg/ml (Figure 4b).…”
Section: In the Thymus Il-1r1 Is Mainly Expressed By Thymic Apcs Undmentioning
confidence: 93%
“…The TCR engagement and co-stimulation critical for Treg induction are provided by unique thymic antigen-presenting cells (APCs). In this respect, the best studied and likely most important thymic APCs for the generation of tTregs are medullary thymic epithelial cells (mTECs) and thymic dendritic cells (t-DCs) [4][5][6] . In addition, common γ-chain cytokines, such as IL-2, are essential for tTreg development [7][8][9][10] , and beyond common γ-chain cytokines, TGF-β was also shown to play a key role 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…The natural importance and therapeutic benefits of regulatory T cells (Tregs) in preventing auto-immune diseases and transplant rejection is becoming more and more accepted [ 167 ]. One important trigger for Treg development is TGF-β-induced Smad 2/3 signaling, which induces expression of the transcription factor forkhead-box-protein p3 (FoxP3), which is essential for lineage commitment.…”
Section: Effects Of Zinc In Immune Cell Signalingmentioning
confidence: 99%
“…The narrowing of the TCR repertoire diversity could be a direct consequence of DP thymocyte death or the result of a functional impairment of thymic antigen-presenting cells (APCs) or simply a decrease in their numbers secondary to IAV-induced thymic atrophy. Thymic APCs are well known to critically contribute to tTreg cell development [45][46][47][48][49], and future studies need to unravel if IAVinduced thymus atrophy results in alterations of the thymic dendritic cell and thymic epithelial cell compartment, which finally affect the TCR repertoire diversity of newly generated T cell subsets. Indeed, it was shown in models of accelerated thymus atrophy and thymus atrophy due to aging that the functionality of thymic APCs was negatively influenced, resulting in a reduced ability to present self-antigens, which perturbed negative selection and finally provoked autoimmune phenotypes [50].…”
Section: The Finding That Ttreg Cell Generation Is Enhanced In the Comentioning
confidence: 99%